PENINGKATAN PRODUKTIVITAS PENGOLAHAN GULA MERAH DARI TEBU DI KECAMATAN KEBONSARI KABUPATEN MADIUN - Larmintho, Rudy Bintoro Hari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The processing of sugar cane into rock sugar in the Ngawi district is a good development of natural products to be utilized in meeting the necessities of life and increasing economic stability. Competition and sales that are not least felt by the owners of sugarcane factories give great consideration to the bankruptcy that will be felt when farmers no longer plant sugarcane in large quantities and even processing quality sugarcane is no longer obtained in large quantities to be processed in sugar factories. The purpose of this research is to increase the production of rock sugar processing with high capacity and good competitiveness through the use of fertilizer with quality no. 1, increase in planting power, involvement of workers in the factory and marketing management in a branding and measurable way. The research method uses a descriptive qualitative approach to literature study design. Data analysis using online journal literature and e-books. The results showed that the largest production in Indonesia was sugarcane plantations of more than 450 thousand hectares, consisting of smallholder sugarcane plantations (TR), State Large Plantations (PBN), and Large Private Plantations (PBS) with sugar production reaching 2.5 million tons. Sugar factories are located in almost every district. The total area planted with sugar cane in East Java is between 170,000-220,000 ha.